PENGARUH PELATIHAN DAN PENEMPATAN PEGAWAI TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KOTA PEMATANGSIANTAR - Marbun, Sarah Fransisca; Lie, Darwin; Butarbutar, Marisi; Nainggolan, Lora Ekana (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
The purpose of this study are: 1. To know the description of training, employee placement and employee performance at Badan Kepegawaian Daerah Pematangsiantar City. 2. To determine the influence of training and employee placement on employee performance at Badan Kepegawaian Daerah Pematangsiantar City either simultaniously or partially.The results of this study can be concluded as follows: 1. Employees states that raining, employee placement, and employee performance is good. 2. Training and employee placement have a positive influence on employee performance. 3. There is moderately high correlation between training and employee placement with employee performance. Then employee performance can be explained by the training and employee placement, 4. Hypothesis stated H0 rejected, meaning training and employee placement have a positive and significant impact on employee performance at Badan Kepegawaian Daerah Pematangsiantar City either simultaneously or partially.Â Keywords: Training, Employee Placement And Employee Performance